2022
DOI: 10.3390/ph15060743
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo and In Vitro Antioxidant Activity of Less Polar Fractions of Dasycladus vermicularis (Scopoli) Krasser 1898 and the Chemical Composition of Fractions and Macroalga Volatilome

Abstract: The present research is a comprehensive investigation of Dasycladus vermicularis (Scopoli) Krasser 1898 from the Adriatic Sea (Croatia) regarding volatilome–volatile organic compounds (VOCs, mostly nonpolar compounds) and less polar nonvolatile compounds for the first time. Headspace solid-phase microextraction (HS-SPME) and hydrodistillation (HD) were used showing the great volatilome variability among fresh (HS-FrDV and HD-FrDV) and dried (HS-DrDV and HD-DrDV) samples after GC–MS analysis. Aromatic aldehydes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(50 reference statements)
1
0
1
Order By: Relevance
“…When compared, F3 fractions contained fatty acid amides, namely erucamide and 9-octadecenamide, which could be associated with a negative impact on zebrafish embryonic development. Similar effects were observed in the recent studies on macroalgae Ericaria crinita , E. amentacea [ 32 ], and Dasycladus vermicularis [ 63 ]. Furthermore, the detected higher toxicity of the D. dichotoma F3 fraction in comparison to the D. fasciola F3 fraction could be ascribed to higher amounts of terpenoids detected by HPLC-HRMS.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…When compared, F3 fractions contained fatty acid amides, namely erucamide and 9-octadecenamide, which could be associated with a negative impact on zebrafish embryonic development. Similar effects were observed in the recent studies on macroalgae Ericaria crinita , E. amentacea [ 32 ], and Dasycladus vermicularis [ 63 ]. Furthermore, the detected higher toxicity of the D. dichotoma F3 fraction in comparison to the D. fasciola F3 fraction could be ascribed to higher amounts of terpenoids detected by HPLC-HRMS.…”
Section: Discussionsupporting
confidence: 89%
“…Non-targeted analysis revealed several components that were most pronounced in D. fasciola F4, including pigment pheophytin b and ceramides known for their antioxidant, anti-aging, anti-inflammatory, and immune regulatory properties [ 68 ]. Compared to the literature, the obtained IC 50 values for both samples were higher than IC 50 values of brown macroalga D. vermicularis F3 and F4 (8.0-fold higher for D. dichtoma F3, and 17.5- and 3.0-fold higher for D. fasciola F3 and F4 sample, respectively) [ 63 ]. Additionally, a recent study reported lower IC 50 values for two Ericaria species when compared to our study [ 32 ].…”
Section: Discussioncontrasting
confidence: 56%
“…22) being the most abundant (Table 1). This PFAA has already been found as the dominant compound in green and brown macroalgae [28,40,41] and in the diatom Skeletonema grevillei [42]. Two other C:18 PFAAa were detected, linoleamide (no.…”
Section: Non-target Screening Of Non-volatile Compounds In Ethanol Ex...mentioning
confidence: 81%
“…From 18.5-25 min, elution was again isocratic at 100% B. Electrospray ionization was set in positive mode (ESI+) with collision-induced dissociation (CID) in informationdependent acquisition mode (IDA) for MS/MS mass spectra acquisition. A detailed description of the parameters can be found in our previous article [40]. The mass spectrometer data were processed using ACD/Spectrus Processor 2021.1.0 software (ACD/Labs, Toronto, ON, Canada).…”
Section: Ultra-high-performance Liquid Chromatography-high-resolution...mentioning
confidence: 99%
“…24) were detected. In our previous studies, we detected oleamide, erucamide, and palmitamide in the green alga Dasycladus vermicularis [40] and two others, palmitoleamide and linoleamide, in the brown algae Ericaria crinita and Ericaria amentacea [28]. The FAAs detected and identified in C. spongiosus belong to the group of primary fatty acid amides (PFAMs) with the structure R-CO-NH 2 , where R represents a long-chain FA [41], and are bioactive signalling molecules.…”
Section: Non-target Screening Of Non-volatile Compounds In Ethanol Ex...mentioning
confidence: 97%